Terahertz Time-Domain Spectroscopic Study of Tricalcium Silicate - Wentao Zhang; Ya Chen; Lidan Tian; Linhao Wang; Xiangyu Li (Sensors, 2022)
In this study, the terahertz (THz) spectra of C3S were obtained in the 0.4–2.3 THz frequency range using different sample preparation methods. In the spectra, a sharp absorption peak of C3S was found at 2.03 THz. Under controlled conditions, the mass ratio of C3S was the most critical factor affecting the strength of the absorption peak, and the absorption coefficient followed the Beer–Lambert law, exhibiting a linear relationship with the mass ratio of C3S. The intrinsic dielectric constants of C3S and polyethylene (PE) were calculated in accordance with the Maxwell–Garnett (MG), Bruggeman (BM), and Landau–Lifshitz–Loovenga (LLL) models, using two-phase composite samples. The results show that the LLL model had the highest accuracy.